Acting anthropologically: Notes on Anthropology as Practice - Cornwall, Andrea (Antropologia Pubblica, 2019)
In this article, I explore the role of anthropology and anthropologists in unsettling orthodoxies and provoking disquiet with taken for granted ways of thinking and doing. Set against the backdrop of the debates about engaged anthropology, my interest is in exploring an approach to anthropology that takes anthropological practice seriously and with it the role of the anthropologist as activist and agent of change. I argue that the work of the anthropologist is not just to do fieldwork and produce texts, but that “engagement” has a more interactive dimension. By acting anthropologically, I suggest, anthropologists can be activists in ways and in settings that are distinct from the kinds of engagement envisaged in contemporary debates on “engaged”, “activist” and “public” anthropology, as well as the modes of practice characteristic of “applied” anthropology. I draw on fragments of auto-ethnography to explore what the idea of acting anthropologically might offer within as well as outside the academy.